Swerve & Shift: The lived experience of Canadian faculty teaching through a pandemic - McDonnell, Maggie; Reid, Erin (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2023)
During the COVID-19 pandemic, which began to affect Canadian universities and colleges in March 2020, educators were asked to make a sudden transition, or swerve, to teaching remotely. Subsequently, these same teachers made the shift to teaching remotely longer term, through the fall and winter of 2020-21; the pandemic continued to affect higher education into 2022. Through interactive interviews, the authors have woven together the individual experiences of teachers in higher education across Canada, and found that these teachers faced unprecedented challenges, as well as unimagined silver linings. Based on Porges’ (1995) model of polyvagal theory, the authors suggest that digital communities of practice (Donaldson 2020) provided a muchneeded site of social engagement to mitigate trauma in these unprecedented times.